Low accuracy of interpretation of rotator cuff MRI in patients with osteoarthritis. (October 2013) - Sershon, Robert A; Mather, Richard C; Sherman, Seth L; McGill, Kevin C; Romeo, Anthony A; Verma, Nikhil N
Abstract : Background Magnetic resonance imaging (MRI) is considered to be a valuable tool for the diagnosis of rotator cuff tears in patients with severe glenohumeral osteoarthritis who are indicated for total shoulder arthroplasty (TSA). We determined the sensitivity, specificity, and positive predictive value of MRI in diagnosing rotator cuff tears in such patients. Methods MRI reports of 100 patients who had completed a shoulder MRI prior to TSA were reviewed to determine the radiologists' interpretation of the MRI including the diagnosis, presence of a full-thickness cuff tear, and the presence of atrophy and/or fatty infiltration within the rotator cuff muscle bellies. Operative reports were used as a gold standard to determine whether a full-thickness rotator cuff tear was present. Results Preoperative MRI reports noted 33 of the 100 patients as having a full-thickness rotator cuff tear, 17 of which had multiple tendon tears. 2 of the 33 patients with full tears on MRI were found to have full-thickness tears at surgery. The sensitivity, specificity, and positive predictive value for MRI detection of full-thickness tears were 100%, 68%, and 6% respectively, with a false-positive rate of 32% and an accuracy of 69%. Interpretation The study suggests that although MRI is highly sensitive, it has a low positive predictive value and moderately low specificity and accuracy in detecting full-thickness rotator cuff tears in patients with severe glenohumeral osteoarthritis.